Assessing post-adoption utilisation of an information technology within a supply chain management context. (14th January 2008) - Lippert, Susan K.
Information Technology (IT) has generated profound effects on Supply Chain Management (SCM) activities related to problem-solving, information sharing, and cost reduction initiatives. The influences of individual-level antecedents on post-adoption utilisation of a specialised IT within an SCM context were examined. Data were collected from 272 first-tier supply chain members of the second largest US automotive service-parts logistics operation using a new supply chain technology. Twelve hypotheses were tested through a structural equation model. The results suggest that in supply chains where usage is mandated, individual-level determinants can increase utilisation. Study implications and suggestions for future research are discussed.